Pengaruh Gaya Kepemimpinan dan Keterampilan Berkomunikasi Kepala Sekolah terhadap Kinerja Guru - Ahmad Gawdy Prananosa; M. Rusni Eka Putra; Armi Yuneti; Rusi Rusmiati Aliyyah (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2018)
This study aims to determine the effect of the principal's leadership style and communication skills on the performance of high school teachers in North Musi Rawas Regency. The research method in this study uses a quantitative approach, using multiple regression analysis. The results of the study used multiple regression analysis with the classical least squares method (Ordinary Least Square), then assumption tests include; multicollinearity, heterokedasticity, autocorrelation, normally distributed. While the statistical hypothesis using the T test and F test. The results of the analysis of variable X1 obtained t-count = 2.644 and p-value = 0.027 / 2 = 0.013 <0.05, meaningful leadership style has a positive effect on teacher performance. Then from the results of the analysis of variable X2 obtained t-count = 2.526 and p-value = 0.013 / 2 = 0.006 <0.05. In conclusion, communication skills have a positive effect on teacher performance. Keywords: Leadership Style, Communication Skills, Performance